Euan W. MacKie, Professor Challenger and his Lost Neolithic World: The Compelling Story of Alexander Thom and British Archaeoastronomy. (18th February 2022) - Brophy, Kenneth
Abstract : Euan W. MacKie, Professor Challenger and his Lost Neolithic World: The Compelling Story of Alexander Thom and British Archaeoastronomy Oxford: Archaeopress, 2020. Paperback 158 pp., 81 figures ISBN 9781784918330. £30.00.